Characteristics of Hospitalized Pediatric Coronavirus Disease 2019 Cases in Chicago, Illinois, March–April 2020. (1st June 2020) - Mannheim, Jonathan; Gretsch, Stephanie; Layden, Jennifer E; Fricchione, Marielle J
Abstract: Background: To date, no report on coronavirus disease 2019 (COVID-19) pediatric patients in a large urban center with data on underlying comorbidities and coinfection for hospitalized cases has been published. Methods: This was a case series of Chicago COVID-19 patients aged 0–17 years reported to the Chicago Department of Public Health (CDPH) from March 5 to April 8, 2020. Enhanced case investigation was performed. χ 2 and Wilcoxon 2-sample tests were used to compare characteristics among hospitalized and nonhospitalized cases. Results: During March 5–April 8, 2020, 6369 laboratory-confirmed cases of COVID-19 were reported to CDPH; 64 (1.0%) were among children aged 0–17 years. Ten patients (16%) were hospitalized, and 7 (70%) required intensive care (median length of hospitalization, 4 days [range, 1–14 days]). Reported fever and dyspnea were significantly higher in hospitalized patients than in nonhospitalized patients (9/10 vs 28/54, P = .04 and 7/10 vs 10/54, P = .002, respectively). Hospitalized patients were significantly younger than nonhospitalized patients (median, 3.5 years vs 12 years; P = .03) and all either had an underlying comorbidity or coinfection. Among the 34 unique households with multiple laboratory-confirmed infections, the median number of laboratory-confirmed infections was 2 (range, 2–5), and 31 (91%) households had at least 1 COVID-19–infected adult. For 15 households with available data to assess transmission, 11 (73%) were adult-to-child, 2 (13%) child-to-child, and 2 (13%) child-to-adult. Conclusions: Enhanced case investigation of hospitalized patients revealed that underlying comorbidities and coinfection might have contributed to severe disease. Given frequency of household transmission, healthcare providers should consider alternative dispositional planning for affected families of children living with comorbidities. Abstract : In the first US urban jurisdiction case series summarizing findings of enhanced case investigation of hospitalized pediatric COVID-19 patients, household transmission was frequent, and all hospitalized patients were found to have an underlying comorbidity or coinfection.